Generation of urban solid waste: application of a sustainability indicator in a municipality of the Alagoas semi-arid (Research, Society and Development, 2020)
The great increase of the human population in the last decades, associated to the diverse anthropic activities, has brought a considerable increase in the generation of residues, mainly urban solid waste (MSW). In order to quantify this appropriation about the environment, several tools have been developed, with special emphasis on the Ecological Footprint (EF), one of the most widespread sustainability indicators in the world today. The present study aimed to analyze the generation and gravimetry of solid urban waste and to apply the Ecological Footprint to the generation of these materials in the municipality of Dois Riachos, Alagoas, and was guided by a descriptive and quantitative research. Data on generation and gravimetry were obtained through the State Solid Waste Plan of the State of Alagoas. The per capita and total EF of the study area were quantified. The results showed a per capita MSW generation rate of 0.57 kg / day per inhabitant, which led to an annual production of 1168 tons, composed mostly of organic material (64.85%). The per capita EF was 0.1166 total hectares (gha), while the total EF of the MSW was 651.41 gha. The Ecological Footprint proved to be an indicator of easy application and interpretation of the results.